Kiken Yochi Training (KYT) in reducing accidents at workplaces: a systematic review - Ya'acob, Noor Afifah; Rasdi, Irniza; Z. A., Emilia; Abdul Rahman, Anita; Ismail, Suriani (Community Health Society Malaysia, 2016)
Objective: The aim of this paper is to systematically review the literature in order to explore the usage and efficiency of Kiken Yochi training (KYT) in reducing workplace accidents. Materials and Methods: Literature was sought from online database. These database included PubMed, Science Direct, JICOSH, and Google Scholar. Only English full text articles published from 2000 to 2015 were selected. The main keywords used for the search were (Kiken Yochi) OR (hazard prediction) AND (work injury) OR (accident) AND (working site accident). In total, six studies met the inclusion criteria for this review. Result: Four studies were from Japan, one study was from Thailand, and one study was from the United States of America (USA). These selected studies used different study designs; cross-sectional, cohort, experimental, quasi-experimental and case study. Respondents involved were factory workers, laboratory workers, students and contractor workers. Implementation of KYT was found to be consistently effective in increasing workers’ awareness on occupational hazards, promoting health and safety practice and reducing occupational accident rate. Involvement of all top managements and employees in decision-making process is the key factor for the success of KYT implementation. Conclusion: In summary, KYT is indeed a promising tool to be implemented in various industries to reduce hazard and accidents at the workplace.